A new model of continuous improvement in total quality management from an Islamic perspective - Afrin, Afroza Bulbul; Islam, Rafikul; Fontaine, Rodrigue Ancelot Harvey; Ali, Md. Yousuf; Rahman, Mizanur (Asian Academy of Management, 2019)
Continuous improvement in products/services is a vital element of Total Quality Management (TQM). To strengthen competitive advantage in the market, organisations must continuously improve quality of products and services. Whether this process is termed Jidoka, Kaizen, PDSA, 5-S, Six Sigma, or JIT, the purpose is to continually improve product/service quality or process quality. However, these models focus solely on mundane benefits. Developing a model of continuous improvement from an Islamic perspective is the major objective of this study. By nature, the study is an exploratory one and theoretically based on library research and is rooted in the Qur’ān and Sunnah. The major outcome of this research is development of a new model of continuous improvement, named NAMS cycle. This cycle is composed of four inter-related components: al-Nīyyah bi al- Ikhlās, al-‘Amal, al-Muḫāsaba and al-Ṣhukr. Having the initial letters of the components the model is named. In turn, each component consists of a number of elements, for example al-Nīyyah bi al- Ikhlās consists of intention, objectives, and planning. Organisations have to fulfil two prerequisites for successful implementation of the model in their premises which are top management commitment and strongly motivated work team.